A new naphthalimide derivative as a selective fluorescent and colorimetric sensor for fluoride, cyanide and CO2. (September 2015) - Lee, Minji; Jo, Sunjung; Lee, Dayoung; Xu, Zhaochao; Yoon, Juyoung
Abstract: A new naphthalimide derivative 1 is reported as an anion-activated CO2 chemosensor. Among the various anions, chemosensor 1 displayed selective colorimetric and fluorescence changes with F − and CN − . Hydrogen bonding interactions between amine groups and anions can be attributed to these changes. The exposure of CO2 revived the original color and fluorescence, so that distinct "On-Off-On" fluorescence emission changes were observed, for this anion-activated CO2 sensing mechanism. Graphical abstract: Highlights: A new naphthalimide derivative 1 showed selective UV/vis absorption and fluorescence changes with F − and CN − . Colorimetric and fluorescence changes of chemosensor 1 with F − or CN − were revived upon exposure to CO2 . We demonstrated a novel anion-activated sensing strategy for CO2 .